PENGARUH SOLVABILITAS, OPINI AUDITOR, UKURAN KAP, DAN KOMITE AUDIT TERHADAP AUDIT DELAY - Apriyani, Nurul Nur (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this research is to examine the signification impact of solvability, auditors opinion, the size of Public Accountant Firms and audit committee influence on audit delay in the manufacturing companies listed on the Indonesia Stock Exchange. The population of this research is manufacturing companies listed in Indonesia Stock Exchange from 2010 to 2013. The sample used in this study are 32 companies with years of observation 4 years so the total sample of 128 who have met the criteria for the determination of the sample using purposive sampling technique. The method of analysis used to test the hypothesis is multiple linear regression analysis with the help of the program SPSS version 13. The Results of this study show that Solvability has a significant influence in a positive direction to the audit delay. Auditor Opinion but not significant effect on audit delay . Firm Size has significant influence with the negative direction of the audit delay and Audit Committee has significant influence with the negative direction of the audit delay. Based Test Capability Determination of independent variables in explaining the variance of the dependent variable in the regression model by 7 percent is explained by other variables outside the model. Keywords: Audit Delay, Solvability, Opinion Auditor, Firm Size, Audit Committee.